2013
DOI: 10.1007/s12288-013-0241-8
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Hemophagocytic Lymphohistiocytosis After Hepatitis A Infection

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a clinical condition which result in cytotoxic Tcell and antigen presenting cell overproduction and also their cytokines. Hepatitis A Virus associated HLH is very rare condition among other viruses. This condition is often difficult to diagnose, so treatment is often delayed. Here we present a case of adolescent boy with secondary virus associated HLH diagnosis with Hepatitis A infection and successfull treatment by short course of intravenous immunoglobulin and ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Full texts were available for 24 cases and only abstracts available for two cases in the articles reviewed. 3,4,626…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full texts were available for 24 cases and only abstracts available for two cases in the articles reviewed. 3,4,626…”
Section: Methodsmentioning
confidence: 99%
“…Navamani et al 11 3.5 M India Oral dexamethasone þ cyclosporine Alive Navamani et al 11 9 F India IV dexamethasone þ cyclosporine Alive SJIA Canoz et al 12 10 M Turkey IVIg þ dexamethasone Alive Onaga et al 13 19 F Japan IV methylprednisolone Alive Bay et al 15 1 M Turkey IVIg Alive Bay et al 15 11 M Turkey IVIg Alive Das et al 16 4 M India Dexamethasone Alive Kondo et al 17 49 F Japan Methylprednisolone þ G-CSF Alive Lee et al 18 26 21 20 F England Hydrocortisone þ IVIg Alive SJIA Russo et al 22 3 F Argentina Dexamethasone þ etoposide Alive SJIA Tai et al 23 32 M Taipei Steroid, cyclosporine þ etanercept Alive Alhaddad et al 25 19 F Egypt IV methylprednisolone Alive Kaur et al 10 6 F India IV dexamethasone Died HEV co-infection Choudhary et al 14 5 F India Etoposide, dexamethasone þ cyclosporine Died HEV co-infection Ishii et al 19 37 M Japan Plasma exchange, methylprednisolone, cyclophosphamide þ vincristine Died Russo et al 22 3 F Argentina Methylprednisolone, cyclosporine þ etanercept Died SJIA Wu et al 24 23 M China Steroid Died HCV infection Park et al 26 28 F South Korea NA Died HCV, hepatitis C virus; HEV, hepatitis E virus; IVIg, intravenous immunoglobulin; SJIA, systemic juvenile idiopathic arthritis.…”
Section: Fundingmentioning
confidence: 99%
“…Moreover, HLH can result from infection with hepatitis viruses, with the majority of cases involving HAV and, less commonly, HBV or HCV infection [92][93][94]. Two systematic reviews of HAV-associated HLH cases have identified hepatomegaly and splenomegaly as distinguishing features of HAV-HLH, as these signs are rarely observed in patients with HAV infection who do not develop HLH [63,95].…”
Section: Hepatitis Virusesmentioning
confidence: 99%